An object-oriented design method to implement the mechatronic system control by using hybrid automata and real-time UML - Quang, Vu Duy; Hien, Ngo Van (Vietnam Journal of Mechanics, 2011)
In this paper, we present a method, which is based on hybrid automata and Real-Time Unified Modeling Language (UML) to analyze and design the control parts of mechatronic systems with input or output events and signals in order to effectively gather their structure and behaviour. We introduce step-by-step analysis and design activities of a controlled mechatronic system such as the specification of its hybrid automaton and realization hypotheses, the identification of object collaborations of this system, the identification of main control capsules, their ports and communication protocols, with their static and dynamic links. These activities are conducted by specializing the iterative life cycle of system development. Then, we indicate important hypotheses, which allow all the identified capsules of this system to make their evolutions. We apply this method to develop an Electro-Hydraulic Governor (EHG) system, which allows the frequency of an electro-hydraulic station to be stabilized.